MODEL MATEMATIK PENGERINGAN LAPIS TIPIS WORTEL - Setyopratomo, Puguh (Jurnal Teknik Kimia, 2012)
Drying is one of the most significant method in food preservation. This study was conducted to investigate mathematical models of thin layer drying of carrot slices. The kinetic of thin layer drying of carrot slices was experimentally investigated in a hot air convective dryer. Crank solution for difusion in slab model for drying in thin layer were used to predict the drying profile. Drying characteristic of carrot slices were determined using air at 50 oC , 60 oC, 70 oC and  80 oC at air linier velocity  0.4167 m/s. The result showed that before material deformation was taken place the Crank solution model was suitable for long- periode drying. Key words: carrot, drying, mathematical model